Light and heavy ion beam analysis of thin biological sections - Lee, J.; Siegele, R.; Pastuovic, Z.; Hackett, Mark; Hunt, N.; Grau, G.; Cohen, D.; Lay, P. (Elsevier, 2013)
The application of ion beam analysis (IBA) techniques to thin biological sections (ThBS) presents unique challenges in sample preparation, data acquisition and analysis. These samples are often the end product of expensive, time-consuming experiments, which involve many steps that require careful attention. Analysis via several techniques can maximise the information that is collected from these samples. Particle-induced X-ray emission (PIXE) and Rutherford backscattering (RBS) spectroscopy are two generally non-destructive IBA techniques that use the same MeV ions and can be performed simultaneously. The use of heavy ion PIXE applied to thick samples has, in the past, resulted in X-ray spectra of a poorer quality when compared to those obtained with proton beams. One of the reasons for this is the shorter probing depth of the heavy ions, which does not affect thin sample analysis. Therefore, we have investigated and compared 3-MeV proton and 36-MeV carbon ion beams on 7-µm thick mouse brain sections at the ANSTO Heavy ion microprobe (HIMP). The application of a 36-MeV C4+ ion beam for PIXE mapping of ThBS on thin Si3N4 substrate windows produced spectra of high quality that displayed close to a nine-times gain in signal yield (Z2/q) when compared to those obtained for 3-MeV protons for P, S, Cl and K but not for Fe, Cu and Zn. Image quality was overall similar; however, some elements showed better contrast and features with protons whilst others showed improved contrast with a carbon ion beam. RBS spectra with high enough counting statistics were easily obtained with 3-MeV proton beams resulting in high resolution carbon maps, however, the count rate for nitrogen and oxygen was too low. The results demonstrate that on thin samples, 36-MeV C4+ will produce good quality PIXE spectra in less time; therefore, carbon ions may be advantageous depending on which element is being studied. However, these advantages may be outweighed by the inherent disadvantages including increased ion beam damage, the necessity of very high ion energies resulting in higher neutron fields. © 2013 Published by Elsevier B.V. All rights reserved.